Creating 'advantageous' spaces for migrant and refugee youth in regional areas: a local approach. Issue 3 (4th May 2021) - Barnes, Melissa
ABSTRACT: To alleviate overpopulation in Australia's metropolitan areas and counter population decline in regional areas, regional settlement of newly arrived migrants and refugees has emerged in recent policy debates. With a new federal government plan to introduce mandatory regional settlement for migrants, significant responsibility is placed on regional schools to cater for the unique needs of students from linguistically and culturally diverse backgrounds. Evoking Bourdieu's thinking tools, this paper examines the perspectives of principals and teachers from two regional schools in Victoria, Australia by exploring their beliefs and dispositions towards English as an Additional Language (EAL) students in mainstream classrooms and their capacity to build student capital within a regional education field. This paper argues that for regional settlement to be 'advantageous', regional schools must look from within to initiate a whole school approach to EAL support and professional development and promote community connections to create advantageous spaces for migrant and refugee youth.